The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1159/000264837
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Eye Infections Caused by Pseudomonas aeruginosa

Abstract: Cells of Pseudomonas aeruginosa were titered (1.0× 104–1.0× 108 cells) to determine the minimum number required to initiate corneal infection in Swiss-Webster and BALB/c mice. No infection was produced in either strain of mouse by direct application of the organisms to unwounded corneas. However, wounding the cornea in either strain followed by application of the bacteria (1 × 107–1 × 108 cells) produced corneal infection within 18–24 h. In Swiss-Webster mice, cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…Many clinical features of the disease are reproducible in rodent models, including the rat (4) and mouse (5,6). The mouse scarification model of Pseudomonas keratitis has been well characterized, and the genetic susceptibility of C57BL/6 (B6) 3 (7) and related inbred strains (8) to eye infection resulting in perforation of the cornea and blindness correlated with a CD4 ϩ T cell (Th1)-regulated inflammatory response.…”
mentioning
confidence: 99%
“…Many clinical features of the disease are reproducible in rodent models, including the rat (4) and mouse (5,6). The mouse scarification model of Pseudomonas keratitis has been well characterized, and the genetic susceptibility of C57BL/6 (B6) 3 (7) and related inbred strains (8) to eye infection resulting in perforation of the cornea and blindness correlated with a CD4 ϩ T cell (Th1)-regulated inflammatory response.…”
mentioning
confidence: 99%
“…Many clini cal features of the disease can be experimen tally produced and have been studied in mice [2,3], rats [4] and rabbits [5], Previous studies have shown that inbred mouse strains, such as DBA/2J and DBA/1J [6][7][8][9], as well as outbred Swiss-Webster [3] mice topically infected onto the sacrificed cornea with pseudomonas were able to resolve the bacterial infection, to re store corneal clarity and hence were classed as resistant. Other mouse strains.…”
mentioning
confidence: 99%
“…Other mouse strains. C57BL/6J, C3H/HeJ and A/J failed to restore corneal clarity following similar bacterial challenge and were classed as susceptible [6][7][8][9], In sev eral animal species, including the mouse, the response to pseudomonas ocular challenge has been shown histologically to consist almost entirely of a local infiltration of PMN and few mononuclear cells [3][4][5][10][11][12]], Yet, no study has systematically examined and character ized the distribution and kinetics of the in flammatory cell response to pseudomonas ocular challenge beyond the initial few days.…”
mentioning
confidence: 99%
“…The rise in its occurrence has been attributed to the increased use of extended-wear contact lenses (7,12). Following adherence of the organism to a damaged corneal epithelium (14,29), the release of exogenous enzymes, including proteases (16), elastases (16,24), and exotoxins (1,13,15), is necessary for stromal penetration of the organism to occur. Evidence suggests that these enzymes contribute to corneal destruction (3,16,18,24) and that their inhibition may lead to a reduction in the amount of corneal destruction which occurs (17,22,23).…”
Section: Methodsmentioning
confidence: 99%